Mediator Effect between Leadership Style and Organizational Effectiveness of Employee Commitment: A Malaysian Perspective - ISA, KHAIRUNESA; PALPANADAN, SARALA THULASI (International Journal of Psychosocial Rehabilitation, 2020)
Past research has mostly focused on the impact of leadership style on organizational effectiveness. However, the role of employee commitment such as absenteeism, turnover or discipline problem as a mediator has been neglected. Thus, the objective of this study is (i) to determine the relationship between the transformational and transactional leadership style and the organizational effectiveness, and (ii) to identify the effect of employee commitment as a mediator, either as partial or full mediator in the relationship between the leaders’ behaviours. A total of 130 public service officers were selected based on purposive sampling to participate in a survey. The instruments used were the Multifactor Leadership Questionnaire to measure the respondents’ perceptions towards the transformational and transactional leadership style, a Three-Component Model of Employee Commitment to measure the employees’ commitment, and Index of Perceived Organizational Effectiveness to measure the organizational effectiveness. Frequency distribution and percentages to describe the respondents’ demographics were analysed using descriptive statistics while the relationship between the transformational and transactional leadership style and the organizational effectiveness were analysed using Pearson Correlation and Multiple Regression. To determine the effect of employee commitment as a mediator, three regression equations based on Baron and Kenny model were run through Multiple Regression Analyses. The results revealed that employee commitment was found to have a partial mediator effect in the relationship between leadership style and effectiveness of the organization. This study provided some insights on the importance of leadership style and the effect of employee commitment to enhance the effectiveness of an organization. Keywords: employee commitment, leadership style, mediator effect, organization effectiveness. Past research has mostly focused on the impact of leadership style on organizational effectiveness. However, the role of employee commitment such as absenteeism, turnover or discipline problem as a mediator has been neglected. Thus, the objective of this study is (i) to determine the relationship between the transformational and transactional leadership style and the organizational effectiveness, and (ii) to identify the effect of employee commitment as a mediator, either as partial or full mediator in the relationship between the leaders’ behaviours. A total of 130 public service officers were selected based on purposive sampling to participate in a survey. The instruments used were the Multifactor Leadership Questionnaire to measure the respondents’ perceptions towards the transformational and transactional leadership style, a Three-Component Model of Employee Commitment to measure the employees’ commitment, and Index of Perceived Organizational Effectiveness to measure the organizational effectiveness. Frequency distribution and percentages to describe the respondents’ demographics were analysed using descriptive statistics while the relationship between the transformational and transactional leadership style and the organizational effectiveness were analysed using Pearson Correlation and Multiple Regression. To determine the effect of employee commitment as a mediator, three regression equations based on Baron and Kenny model were run through Multiple Regression Analyses. The results revealed that employee commitment was found to have a partial mediator effect in the relationship between leadership style and effectiveness of the organization. This study provided some insights on the importance of leadership style and the effect of employee commitment to enhance the effectiveness of an organization.